Pemberian Asupan Gizi Seimbang terhadap Pertumbuhan dan Perkembangan Anak Usia Dini - Setiaarwati, Anov; Wahyudin, Erik (Mulya Literasi Publishing, 2024)
This study aims to determine the effect of the application of balanced nutritional foods on early childhood growth and development at Sindang State Kindergarten. This study uses a Quantitative research method with a survey type. This method is used in evaluation to make a systematic, factual, and accurate description of the facts and properties of a particular population or area. The total research population was 33 children, then taken using purposive sampling so that the research respondents became 15 children. The instruments used in this study used observation sheets in the form of checklists with data collection through observation, documentation, and structured questionnaires regarding the effect of the application of balanced nutritional feeding on early childhood growth and development. The data analysis technique used a simple linear regression test using the help of the SPSS technique. This research data analysis technique tests validity, descriptive statistics, normality, homogeneity, simple linear regression, correlation, and dependent sample tests using statistics with the help of SPSS. Based on the results of this study there is a significant effect of balanced nutritional feeding on early childhood growth and development in Sindang State Kindergarten. This is evidenced based on the Ftable results calculated using the f test with a sig of 0.05 is 2.70 so that fcount>ftable (9.006> 4.543). This shows that Ha is accepted Ho is rejected, which means that providing balanced nutritional food has a positive and significant effect on the growth and development of children after early age at TK Negeri Sindang.